2008
DOI: 10.1243/09576509jpe569
|View full text |Cite
|
Sign up to set email alerts
|

Laminar flamelet model prediction of NOx formation in a turbulent bluff-body combustor

Abstract: A bluff-body combustor, with recirculation zone and simple boundary conditions, is ideal as a compromise for an industrial combustor for validating combustion models. This combustor, however, has proved to be very challenging to the combustion modellers in a number of previous studies. In the present study, an improved prediction has been reported through better representation of turbulence effect by Reynolds stress transport model and extended upstream computational domain. Thermo-chemical properties of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…Fine-tuning of the standard k-ε model constants can also be found in [6][7][8] in conjunction with EDC combustion model, where acceptable accuracy is reported. When used with laminar flamelet model, both the fine-tuned k-ε model and the RSM yielded acceptable results as reported in [10] and [11] respectively. Yilmaz et al [9] compared the fine-tuned k-ε model with large eddy simulation (LES) with two subgrid models; the Smagorinsky-Lilly and RNG/k-ε models.…”
Section: Turbulence Modelingmentioning
confidence: 73%
See 3 more Smart Citations
“…Fine-tuning of the standard k-ε model constants can also be found in [6][7][8] in conjunction with EDC combustion model, where acceptable accuracy is reported. When used with laminar flamelet model, both the fine-tuned k-ε model and the RSM yielded acceptable results as reported in [10] and [11] respectively. Yilmaz et al [9] compared the fine-tuned k-ε model with large eddy simulation (LES) with two subgrid models; the Smagorinsky-Lilly and RNG/k-ε models.…”
Section: Turbulence Modelingmentioning
confidence: 73%
“…The steady laminar flamelet model is known to perform better in terms of prediction of minor species. Several researchers [9][10][11] have used such model to simulate similar flames of CH 4 /H 2 . Yilmaz et al [9] calculated the Probability Density Function (PDF) for temperature, mixture fraction and major and minor species mass fractions and compared the flamelet model with equilibrium model, showing that flamelet model yields better results within the reaction zone.…”
Section: Modeling Of Turbulent Hydrogen Enriched Combustionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar flame was simulated with the eddy dissipation concept (EDC) by Frassoldati et al [24] and Mardani and Tabejamaat [25] and an unacceptable accuracy was found for mass fraction of minor species like O and OH which conducts to wrong expectation for NO formation behavior. It was found that, for modelling the combustion of hydrogen-enriched methane, the steady laminar flamelet method has better performance in terms of minor species prediction [26]. Probability density function (PDF) was calculated for mass fraction of minor and major species, mixture fraction, and temperature by Suo [27].…”
Section: Hydrogen-enriched Gaseous Fuel Combustion Modellingmentioning
confidence: 99%